Comparative Study on the Comfort of Public Space in Residential Settlement (Case Study: RBRA Kalpataru & RPTRA Anggrek) - Wenny Arminda (Jurnal Arsitektur TERRACOTTA, 2023)
In addition to its roles as a water catchment and green space, a city's public space is a location for people to congregate and participate in activities together. For these reasons, public space is a vital component of the design of a city. As study objects, we will be using Child-Friendly Playrooms (RBRA) Kalpataru and Child-Friendly Integrated Public Spaces (RPTRA)Anggrek in our investigation. It is anticipated that the availability of child-friendly public places would facilitate the fulfilment of children's rights, making it possible for them to live, grow, develop, and engage in social activities to the fullest extent possible. The primary topics discussed in this research are the design and requirements of both public spaces in communities with varied environmental and cultural settings. Observation and interviews are the methods that were used in this investigation. This research aims to discover how the general population feels about the comfort level in public spaces. Aspects of thermal comfort, safety, circulation, amenities, noise, and view are evaluated as part of the comfort assessment. RPTRA Anggrek was found to have a comfort level with an average score of 94.5 (very good), which was higher than RBRA Kalpataru, which got an average score of 68 (moderate).